A contribution to the biology of the sociable weaver Philetairus socius (Latham) - Maclean, Gordon L (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1967)
Anyone who has travelled the dusty road in the bed of the Kuruman River from Kuruman in the Northern Cape to the South West African border at Rietfontein cannot fail to have been impressed by the large communal nests of the sociable weaver Philetairus socius which adorn many of the camelthorn trees along the way. One of the earliest reports of the bird and its nest is that of Sir Andrew Smith (1849) who passed that way through what was then Latakoo (the present day Kuruman), collecting birds which he described for the first time. To him we are indebted for the first published illustrations of the sociable weaver, its nest and egg, and a brief account, not entirely accurate to be sure, of the building and occupation of the nest. This account has since been quoted at length by Shelley (1905) and by Friedmann (1930a) who accepted Smith's statements as they stood. Some years after Smith's travels, Anderson wrote (1872) that the flocks of sociable weavers " ... incubate their eggs under the same roof, which is composed by these birds of whole cartloads of grass piled on a branch of some kamel-thorn tree in one enormous mass of an irregular umbrella-shape, looking like a miniature haystack, and almost solid, but with the under surface, which is nearly flat, honeycombed all over with little cavities, which serve not only as places for incubation but also as a refuge against rain and wind". This account gives some idea of the spectacular nests built by these birds which are hardly larger than a sparrow. But, living in the dry and thinly-populated western regions of southern Africa, the sociable weaver remained a remote curiosity, the subject of casual reports and some strange ideas. Since Friedmann (1930a) studied the sociable weaver briefly in the western Transvaal, the only thorough field observations (mainly on nests and nest sites) up to the present have been those of Rudebeck (1953, 1956). Collias & Collias (1964) returned to the western Transvaal some 20 years after Friedmann's visit, but unfortunately had time for only a cursory study; their main interest was once again in the nest and its architecture. Thus, in 1964 when I joined Dr. T.J. Cade, then of Syracuse University and now of Cornell University, on his desert biology programme, he suggested that the sociable weaver be the subject of special study in the Kalahari. Here was a bird, resident in a harsh environment, living throughout the year in an extraordinary nest, and almost completely unknown biologically. Among the questions to be answered were: How is the nest started and how is it constructed? Which birds build, and how is the labour organized? What is the purpose of the elaborate nest: does it provide a micro-climate which enables the birds to survive better under arid conditions? How could such a communal nest have evolved? What is the social organization of the colony in and out of the breeding season? When do the birds breed and what factors induce breeding? What happens to the young birds after they become independent of their parents? Naturally many other questions arose as the work proceeded, but these were the main ones on which the project was initiated.
Keywords: Weaverbirds